Origin of near to middle infrared luminescence and energy transfer process of Er3+/Yb3+co-doped fluorotellurite glasses under different excitations - Huang, Feifei; Liu, Xueqiang; Ma, Yaoyao; Kang, Shuai; Hu, Lili; Chen, Danping (Scientific reports, 2015)
We report the near to middle infrared luminescence and energy transfer process of Er 3+ /Yb 3+ co-doped fluorotellurite glasses under 980, 1550 and 800 nm excitations, respectively. Using a 980 nm laser diode pump, enhanced 1.5 and 2.7 μm emissions from Er 3+ :I 13/2 → 4 I 15/2 and I 11/2 → 4 I 13/2 transitions are observed, in which Yb 3+ ions can increase pumping efficiency and be used as energy transfer donors. Meanwhile, Yb 3+ can also be used as an acceptor and intensive upconversion luminescence of around 1000 nm is achieved from Er 3+ :I 11/2 → 4 I 15/2 and Yb 3+ : F 5/2 → 4 F 7/2 transitions using 1550 nm excitation. In addition, the luminescence properties and variation trendency by 800 nm excitation is similar to that using 1550 nm excitation. The optimum Er 3+ and Yb 3+ ion ratio is 1:1.5 and excess Yb 3+ ions decrease energy transfer efficiency under the two pumpings. These results indicate that Er 3+ /Yb 3+ co-doped fluorotellurite glasses are potential middle- infrared laser materials and may be used to increase the efficiency of the silicon solar cells.